The Solar Flashing Light / Zuhaila Abdul Halim and Shahida Shaharuddin - Abdul Halim, Zuhaila; Shaharuddin, Shahida (2003)
Solar energy- is one kind of energy that existed. It is a reusable source since we get it direct from the sun. Solar energy- is economical as heat from the sun is free and the cost is far less than using other sources like current source. Our project, the Solar Flashing Light is applicable in Malaysia because of our geographical location that near the equator line: the heat of broad daylight is high. The Solar Flashing Light is divided to two parts: battery- charger and the output (flashing light). The battery charger will charge the rechargeable battery from the solar panel. The solar charger circuit contains one IC and other components such as resistors, preset resistor, transistor, diodes and PCB terminal block. The IC used in this circuit is shunt regulator formed by type TL431LP precision voltage regulator from National Semiconductor. The diodes used here are the high-power series diode and Schottky diode. The transistor used here is power Darlington by type TIP147. In this project, the energy is used to perform flashing light from LED. This flashing output can be applied to highway roads and airplane highways for traffic beneficial.